1984
DOI: 10.1007/bf00695604
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between specific gravity, water content, and serum protein extravasation in various types of vasogenic brain edema

Abstract: Vasogenic brain edema was induced in cats by cold injury (six animals), brain tumors (five animals), and brain abscesses (six animals). Water and electrolyte content, specific gravity, blood volume, and the amount of extravasated serum proteins were determined in small tissue samples taken from gray and white matter at various distances from the lesion. Edema was strictly confined to the white matter of the affected hemisphere and declined from the lesion to the more peripheral regions. It was characterized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(40 citation statements)
references
References 17 publications
0
40
0
Order By: Relevance
“…Therefore, we corrected for the density of brain tissue in our BBPC calculation. A density of mouse brain of 1.04 g/mL was adopted from Bothe et al (1984), and the BBPC was calculated using Equation (2):…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we corrected for the density of brain tissue in our BBPC calculation. A density of mouse brain of 1.04 g/mL was adopted from Bothe et al (1984), and the BBPC was calculated using Equation (2):…”
Section: Methodsmentioning
confidence: 99%
“…sene-bromobenzene gradient columns to determine the specific gravity of brain tissue was first described by Nelson et al [23]. The method has subsequently been adapted for the quantification of brain edema [3,4,6,18,26,30,34]. Methodological studies have shown that reliable results can be obtained when purity of solu tions, temperature of the column, size of tissue samples, and recording time are held constant [8].…”
Section: Discussionmentioning
confidence: 99%
“…A possible cause of tissue osmolality elevation is an oncotic pressure increase resulting from disruption of the blood-brain barrier. 4,9,30,34 Cerebral contusion can increase vascular permeability, leading to leakage of large molecules, such as albumin, from plasma to contused tissue. However, an immunohistochemical study of the postmortem brain from patients with contusion failed to reveal any plasma protein leakage around contused brain areas during this early period.…”
Section: Experimental Investigationsmentioning
confidence: 99%